A CRYSTAL-CHEMICAL INVESTIGATION OF CR SUBSTITUTION IN MUSCOVITE BY XANES SPECTROSCOPY - Cardelli A.; Cibin G.; Benfatto M.; Marcelli A.; Della Longa S.; Brigatti M.F. (My University, 2003)
This work introduces a novel procedure to fit the scattering features of XANES spectra. The procedure was applied and validated on a chromium-containing muscovite for which structural and crystal-chemical characterization is available from literature. The simulation, which involved clusters formed by up to 90 atoms, proved to be effective in representing the Cr local environment, even if the system is characterized by a very low metal content, as demonstrated by the extremely good correspondence with experimental data.
Keywords: Cr K-edge; XANES spectroscopy; Chromium-containing muscovite